2022
DOI: 10.1007/s12011-022-03353-w
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bentonite Clay, Date Pit, and Chitosan Nanoparticles as Promising Adsorbents to Sequester Toxic Lead and Cadmium from Milk

Abstract: Evaluating residual lead (Pb) and cadmium (Cd) levels in food products, especially milk, is critical for product safety and quality. In this purview, the current study aims to determine Pb and Cd concentrations in milk using atomic absorption spectrophotometry and compare their values with international standards. In addition, it aims to remove these metals from milk samples using low-cost, naturally occurring materials, such as bentonite, date pit, and chitosan nanoparticles. The ability of potential adsorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The deformation of the O-H bond of the water molecules in the small band at 1640 cm -1 is seen. Also, OH stretching bands are observed in the 3628 cm -1 bands [7]. In the spectrum of pectin, the C-H bending vibration can be observed in the peak around 551 cm -1 .…”
Section: Ft-irmentioning
confidence: 93%
See 2 more Smart Citations
“…The deformation of the O-H bond of the water molecules in the small band at 1640 cm -1 is seen. Also, OH stretching bands are observed in the 3628 cm -1 bands [7]. In the spectrum of pectin, the C-H bending vibration can be observed in the peak around 551 cm -1 .…”
Section: Ft-irmentioning
confidence: 93%
“…Also, cadmium leads to persistent rhinitis, eosinophilia, non-hypertrophic emphysema, anosmia, anemia, and persistent osteoporosis. Copper also causes digestive disorders [4][5][6][7]. There are various technologies for purifying environments contaminated with heavy metals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bands at 458 and 513 cm −1 are attributed to (Al-O-Fe) and (Al-O-Si) bending vibrations, respectively [32]. Abdelnaby et al [44] found that bond O-H deformation of the contained water molecules in the silicate matrix is related to the small band at 1633 cm −1 . The band at 1428.18 cm −1 corresponds to the bending vibration of the Al-OH and Si-OH bonds in the octahedral and tetrahedral sheets of the bentonite structure.…”
Section: Ft-ir Spectroscopymentioning
confidence: 99%
“…5. The surface of raw bentonite has a porous structure which increases the contact area and promotes adsorption at active sites of the positively charged ions [44]. It is evident that bentonite clay particles were made up of heterogeneous aggregates of assorted sizes and shapes.…”
Section: Morphological Structure Of Prepared Adsorbentsmentioning
confidence: 99%